The Impact Use of Information Technology, Decision Making, Orientation of Technology, Investment, Perceptions on Organizational Performance. Study on The Tourism Industry in Jogjakarta Indonesia - R. Heru Kristanto HC (Technium Social Sciences Journal, 2020)
This research aims to analyze the impact usage, perception of IT, technology orientation, level of investment and future orientation on against organizational performance. The object of research in the Tourism Industry, Tourism manager in Jogjakarta Indonesia. This research model uses mediation regression. Explanatory factor analysis using the SEM - PLS model statistical tools. The results showed that: 1) The use of information technology has an effect on organizational performance. 2) Information technology for decision making affects organizational performance. 3) Future orientation affects organizational performance. 4) The level of investment has an effect on future orientation. 5) Perceptions of information technology have an effect on future orientation. 6) The use of information technology has an effect on future orientation. 7) Technology orientation affects organizational performance. 8) The level of investment has an effect on technology orientation. 9) Perceptions of information technology affect technology orientation.